Pengaruh Penyuluhan Personal Hygiene Terhadap Pengetahuan dan Sikap Personal Hygiene Saat Menstruasi Pada Siswi Kelas VII Di SMP Negeri 5 Karanganyar - Sari, Yessy Lela; , Dr. Faizah Betty Rahayuningsih, A.S.Kep.M.Kes (2017)
Reproductive health is a component of general th.eproductive health needs special attention especially among teenagers especially a perempuan.WHO stressed the importance of reproductive health education of young adolescents (younger adolescents) in the age group 10-14 years, because at that age is a golden period to form a strong foundation in the adolescent self as a base making wise decisions in the act. The purpose of this study was to determine the knowledge and attitude of students of Class VII in SMP Negeri 5 Karanganyar about personal hygiene during menstruation whether there is influence or increase before and after counseling. This type of research is quantitative, with pre-experimental method, pre-post test design without control group (one group pre and post test design) one group of experiment given intervention. Determination of the size of the sample in this study using total sampling technique, that is how the collection of samples based on the number of population of 75 students class VII who have menstruasi accordance with the criteria in which the researcher wanted the research sample. The results showed an average nilkai VII grade students who are menstruating before being given health education about personal hygiene during menstruation knowledge and attitudes of 75.34 at 67.86 and then after being given health education average value of 86.15 knowledge and attitudes of 72.86. Knowledge significance value of 0.000 or p <0.05 and a significance value of 0.000 attitudes or p <0.05. The conclusion shows the influence of personal hygiene education to the level of knowledge and attitude of personal hygiene during menstruation in female students in class VII SMP Negeri 5 KaranganyarKeywords: knowledge, attitudes, personal hygiene, menstruation